2013
DOI: 10.2214/ajr.11.8348
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Source 256-MDCT for Diagnosis of Anomalous Pulmonary Venous Drainage in Pediatric Population

Abstract: MDCT is a fast and noninvasive technique that allows detailed and comprehensive visualization of APVD characteristics in a pediatric population. High-pitch acquisitions with scanners using a high volume of coverage permit low radiation doses and are an accurate modality for assessing these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…The latest technologic advances (such as scanners with a high volume of coverage) have enabled sub-mSv doses with acquisitions lasting less than 1 s. These devices can scan the entire thorax without the need for sedation and can obtain volumetric high-resolution images, even in small children who are unable to follow breathing instructions. [6][7][8][9][10][11][12][13] The effective radiation doses are similar to those for previously reported acquisitions by scanners with high volumes of coverage. In the study performed by Bonelli-Sica and colleagues 6 using 256-slice MDCT (whether with ECG-gated or non-ECG-gated protocol) in pediatric patients with anomalous PV drainage, the overall effective radiation dose was 1.01 mSv (range, 0.13-6.43 mSv), and it was 0.78 mSv (range, 0.13-4.16) in patients younger than 1 year of age.…”
Section: B a Csupporting
confidence: 85%
See 1 more Smart Citation
“…The latest technologic advances (such as scanners with a high volume of coverage) have enabled sub-mSv doses with acquisitions lasting less than 1 s. These devices can scan the entire thorax without the need for sedation and can obtain volumetric high-resolution images, even in small children who are unable to follow breathing instructions. [6][7][8][9][10][11][12][13] The effective radiation doses are similar to those for previously reported acquisitions by scanners with high volumes of coverage. In the study performed by Bonelli-Sica and colleagues 6 using 256-slice MDCT (whether with ECG-gated or non-ECG-gated protocol) in pediatric patients with anomalous PV drainage, the overall effective radiation dose was 1.01 mSv (range, 0.13-6.43 mSv), and it was 0.78 mSv (range, 0.13-4.16) in patients younger than 1 year of age.…”
Section: B a Csupporting
confidence: 85%
“…Compared with first-generation computed tomographic (CT) scanners, multidetector CT scanners-with their high volume of coverage (≥128 slices/gantry rotation)-enable faster and more accurate evaluation of the cardiac and vascular anatomy, with lower radiation exposure. [6][7][8][9][10][11][12][13] In this study, we used high-pitch, dual-source 256-slice MDCTA to evaluate the anatomic features of TAPVC and associated cardiovascular anomalies in a pediatric population, and we report the radiation doses associated with these examinations.…”
mentioning
confidence: 99%
“…[137][138][139][140][141][142] Systemic venous anomalies are also well visualized by cardiovascular CT. [143][144][145] Cardiovascular CT has also been shown to accurately visualize congenital aortic anomalies including interrupted aortic arch and aortic coarctation in both pediatric and adult patients. [146][147][148][149][150][151][152][153] It is particularly useful for evaluation of the aortic arch after endovascular intervention (stent or stent graft) where aneurysm, aortic wall injury or recurrent arch obstruction are relatively common.…”
Section: Patientsmentioning
confidence: 99%
“…The usefulness of cardiac CT and MRI for evaluation of APVR before surgical correction has previously been reported [5][6][7][8][9]. Indeed, both of these non-invasive modalities have excellent correlations with surgical findings, and in many instances give more complete and accurate information when compared to transthoracic or transoesophageal echocardiography [5,7].…”
mentioning
confidence: 96%
“…Indeed, both of these non-invasive modalities have excellent correlations with surgical findings, and in many instances give more complete and accurate information when compared to transthoracic or transoesophageal echocardiography [5,7]. In addition, it has been suggested that high connected pulmonary veins may be missed during surgery in the absence of sufficient preoperative information or due to the reluctance of surgeons to extend dissection around the superior vena cava because of the associated risk of injury to the phrenic nerve [6].…”
mentioning
confidence: 99%